2009
DOI: 10.1016/s1130-6343(09)71156-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de un programa de intervención farmacéutica en pacientes con medicamentos de riesgo renal

Abstract: The results of the study indicate that the application of a pharmaceutical care model based on the prospective validation of drugs with renal risk, very significantly improved the adaptation of dosing regimens in kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our study reveals similar results to other authors on the subject in distinct types of health care institutions. Alvarez Arroyo et al [12] in a hospital-based study with 185 patients (88 in the control group and 97 in the intervention group), found a frequency of dosing inadequacy of 22.5% in the control group and 18.7% in the intervention group. After the pharmaceutical intervention, the frequency of dosing inadequacy went down by 2.1% and this resulted in lower drug expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study reveals similar results to other authors on the subject in distinct types of health care institutions. Alvarez Arroyo et al [12] in a hospital-based study with 185 patients (88 in the control group and 97 in the intervention group), found a frequency of dosing inadequacy of 22.5% in the control group and 18.7% in the intervention group. After the pharmaceutical intervention, the frequency of dosing inadequacy went down by 2.1% and this resulted in lower drug expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, similar designs have been used in other studies [12-14]. To improve outcome reliability, the unanswered physicians’ questionnaires were taken as negative responses to the pharmacists’ recommendations, the DRP was considered unresolved and was then included in the results pool.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations